(untitled) (Research, Society and Development, 2025)
Free gingival graft is a widely established procedure in periodontal plastic surgery, essential for gaining quality, quantity, width, and thickness of keratinized gingiva. Its indication is important for both the stability of implants— specifically, keratinized tissue for peri-implant health—and for the prevention and treatment of gingival recessions in natural teeth. Mucogingival deficiency in teeth can lead to inflammation, aesthetic discomfort, hypersensitivity, root caries, and difficulty in biofilm control. Currently, the autogenous connective tissue graft from the palate is considered the gold standard treatment due to its predictability for root coverage and benefits for maintenance and prognosis in periodontal surgeries. Knowledge of the palatal anatomy is of utmost importance for the dental surgeon to safely apply the chosen surgical technique during incision, respecting noble areas. The objective of this study was to analyze the conditions of the donor site in free gingival grafts.